Hot Water Epilepsy in a Pregnant Woman: A Case Report. (29th November 2010) - Milanlıoğlu, Aysel; Tombul, Temel; Sayın, Refah
Abstract : Hot water epilepsy is a unique form of reflex epilepsy precipitated by the stimulus of bathing with hot water poured over the head. It is mostly seen in infants and children, with a predominance in males. Unlikely, we present a 32-year-old pregnancy woman with the incipient of reflex seizures triggered by pouring hot water over the head while having a bath during the gestation period and treated successfully with carbamazepine 400 mg/day therapy. Hot water epilepsy is known as a benign and self-limited reflex epilepsy, by firstly avoiding hot water or long showers and secondly using intermittent benzodiazepines or conventional antiepileptic drugs, may be sufficient to be seizure-free.